Income growth and its distribution from Eisenhower to Obama: The growing importance of in-kind transfers - Richard Burkhauser; Kevin C. Corinth; James Elwell (American Enterprise Institute (AEI), 2019)
Using Census Bureau estimates of the market value of in-kind transfers and Current Population Survey (ASEC-CPS) data over the period 1979 to 2007, Burkhauser et al. (2012b) construct measures of income and its distribution.
Keywords: A; 330